PHYSICAL EDUCATION IN EARLY CHILDHOOD EDUCATION IN MARINGÁ-PR: CONSTRUCTION AND IMPLEMENTATION OF AN EDUCATIONAL PUBLIC POLICY - Silvia Bandeira da Silva-Lima; Walcir Ferreira-Lima; Flávia Évelin Bandeira-Lima; Amauri Aparecido Bassoli de Oliveira; Claudio Kravchychyn; Ieda Parra Barbosa-Rinaldi (Journal of Physical Education)
ABSTRACT This research aimed to describe and analyze the process of structuring and implementing Law No. 8392/2009, of the Municipality of Maringá-PR, which includes Physical Education as a mandatory component in the Early Childhood Education curriculum. It is characterized as both a descriptive case and a documentary study, conducted through semi-structured interviews with the researcher in charge and with the parliamentary author of the Law; questionnaires, applied to 27 Physical Education teachers working at Municipal Child Education Centers; and consultation to the legislation and internal documents of the Municipal Department of Education. From the information obtained, it was concluded that the analyzed process took place in a satisfactory way, consolidating the educational public policy in focus.